ELK1 inhibition alleviates amyloid pathology and memory decline by promoting the SYVN1-mediated ubiquitination and degradation of PS1 in Alzheimer’s disease - Lilin Yi; Junjie Li; Yan He; Jiaojiao Wang; Maoju Wang; Song Guo; Man Luo; Bin Wu; Mingliang Xu; Qiuyun Tian; Yepeng Fan; Mulan Chen; et al. (Experimental and Molecular Medicine)
Abstract ELK1 is a member of the E-twenty-six transcription factor family and is usually activated by phosphorylation at Ser383 and Ser389 by extracellular signal-regulated kinase 1/2 (ERK1/2). Dysregulation of ERK1/2 is involved in Alzheimer’s disease (AD)-related neuropathogenesis and cognitive impairments. However, the role of ELK1 in AD pathogenesis remains unclear. Here we report that the expression of ELK1 was significantly increased in the brain tissues of patients with AD and AD model mice. The genetic knockdown of ELK1 or inhibition of its phosphorylation by an interfering peptide (TAT-DEF-ELK1 (TDE)) reduced amyloidogenic processing of APP by targeting PS1, consequently inhibiting Aβ generation and alleviating synaptic and memory impairments in APP23/PS45 double-transgenic AD model mice. In addition, we further found that ELK1 regulated the expression of PS1 by competitively inhibiting the interaction between PS1 and its E3 ubiquitin ligase synoviolin (SYVN1), thereby inhibiting the SYVN1-mediated ubiquitination and degradation of PS1. Our results demonstrate that ELK1 aberrantly increases in AD and genetic or pharmacological inhibition of ELK1 can alleviate AD-related pathology and memory impairments by enhancing the SYVN1-mediated PS1 ubiquitination and degradation, indicating that ELK1 may be a novel target for AD treatment.